2018
DOI: 10.1108/ijm-10-2018-0334
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and outcomes of Hungarian nurses’ career adaptability

Abstract: Purpose With the ageing global population the demand for nursing jobs and the requirements for complex care provision are increasing. In consequence, nursing professionals need to be ready to adapt, obtain variety of skills and engage in career self-management. The purpose of this paper is to investigate individual, micro-level, resources and behaviors that can facilitate matching processes between nursing professionals and their jobs. Design/methodology/approach A survey-based study was conducted among 314 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
0
14
0
2
Order By: Relevance
“…Similar results were found in previous international validation studies. For example, studies with samples from Hungary (concern: 0.79; control: 0.96; curiosity: 0.87; confidence: 0.92; Pajic et al, 2018), Cyprus (concern: 0.77; control: 0.78; curiosity: 0.79; confidence: 0.78; Safavi and Bouzari, 2019), Turkey (concern: 0.87; control: 0.79; curiosity: 0.85; confidence: 0.86; € Oncel, 2014), Iran (concern: 0.80; control: 0.93; curiosity: 0.90; confidence: 0.87; McKenna et al, 2016) and South Korea (concern: 0.80; control: 0.79; curiosity: 0.97; confidence: 0.91; Tak, 2012) found that all items had satisfactory factor loadings (i.e. greater than 0.50) (Kline, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in previous international validation studies. For example, studies with samples from Hungary (concern: 0.79; control: 0.96; curiosity: 0.87; confidence: 0.92; Pajic et al, 2018), Cyprus (concern: 0.77; control: 0.78; curiosity: 0.79; confidence: 0.78; Safavi and Bouzari, 2019), Turkey (concern: 0.87; control: 0.79; curiosity: 0.85; confidence: 0.86; € Oncel, 2014), Iran (concern: 0.80; control: 0.93; curiosity: 0.90; confidence: 0.87; McKenna et al, 2016) and South Korea (concern: 0.80; control: 0.79; curiosity: 0.97; confidence: 0.91; Tak, 2012) found that all items had satisfactory factor loadings (i.e. greater than 0.50) (Kline, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Hussain and Malik (2018) conducted a study on female business students in Pakistan and found that a proactive attitude leads to self-direction and results in a positive perception of career success amongst women. Researchers have studied the relationship between proactive personality and individual-level outcomes, such as career, job satisfaction and performance assessment (Van Dyne and LePine, 1998;Grant and Ashford, 2008), as well as organizational outcomes such as organizational performance (Tornau and Frese, 2013;Pajic et al, 2018). It is, therefore, important to investigate the relationship between proactive career behavior and SCS.…”
Section: Subjective Career Successmentioning
confidence: 99%
“…Apesar dos resultados mistos, pode-se sugerir que a relação tende a ser encontrada, uma vez que chamados geralmente promovem maior autoconsciência e capacidade de adaptação, que são características relevantes para a constituição da empregabilidade (FUGATE; KINICKI; ASHFORTH., 2004). Além disso, chamados têm se mostrado como antecedentes de variáveis como adaptabilidade de carreira (DOUGLASS; DUFFY, 2015) e autoeficácia (KAMINSKY; BEHREND, 2015), que podem ser entendidas como construtos que facilitam a formação da empregabilidade (HUANG, 2015;PAJIC et al, 2018). Assim, propõe-se que: H1: Há uma relação positiva entre perceber um chamado e a empregabilidade.…”
Section: Chamados Ocupacionais E Empregabilidadeunclassified